2016
DOI: 10.2147/ott.s97907
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between EGFR gene polymorphisms and pleural metastasis of lung adenocarcinoma

Abstract: Proliferation, growth, and differentiation of cells are strictly controlled by the signal system of epidermal growth factor receptor (EGFR). If any link of the EGFR signals system is interfered with or damaged, the proliferation, growth, and differentiation of cells would become uncontrolled. EGFR is overexpressed in a variety of malignant tumors, such as non-small-cell lung cancer, colorectal cancer and breast cancer. Results of the study have proved that EGFR overexpression is closely associated with mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
4
5
0
Order By: Relevance
“…Namely, as the process of cell proliferation and differentiation is strictly related to EGFR, tumor metastasis should be affected by variations in EGFR . In line with the expectations, significant differences in genotype and allele frequencies of the -216G/T polymorphism between the patient group with the pleural metastasis in comparison with the nonmetastasis group have been observed [ 100 ]. Based on these findings, the authors have concluded that the polymorphism in exon 13 of the EGFR gene might be one of the molecular mechanisms of pleural metastasis of lung cancer.…”
Section: Ethnicity and Variants Of Egfrsupporting
confidence: 60%
“…Namely, as the process of cell proliferation and differentiation is strictly related to EGFR, tumor metastasis should be affected by variations in EGFR . In line with the expectations, significant differences in genotype and allele frequencies of the -216G/T polymorphism between the patient group with the pleural metastasis in comparison with the nonmetastasis group have been observed [ 100 ]. Based on these findings, the authors have concluded that the polymorphism in exon 13 of the EGFR gene might be one of the molecular mechanisms of pleural metastasis of lung cancer.…”
Section: Ethnicity and Variants Of Egfrsupporting
confidence: 60%
“…Second, due to higher incidences of mutant genes (EGFR, ALK, ROS1, etc.) in ADC [ 26 ], the use of new targeted agents will enhance the response rates and prolong OS. We did not investigate the other rare types of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR, a tyrosine kinase receptor considered to be oncogenic, is responsible for growth, survival, proliferation and differentiation of several cell types. Its activation occurs either through EGF or, in cases of mutations, by the activation of the tyrosine-receptor kinase by other mediators initiating multiple cascades of intracellular events [ 8 , 20 , 27 ]. When altered, either by hyperexpression, amplification or mutations, it induces uncontrolled growth or malignant phenotype, since this pathway physiologically regulates aspects of cell proliferation and survival [ 1 , 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%